Religious Tolerance Through Stone Sculpture Production: The Case of Indonesian Sculptors - Istanto, Riza; Triyanto, T (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2019)
The purpose of this research is to analyze the value of tolerance reflected in the stone-sculpture production in Muntilan. This study used a sociology research approach with an ethnographic research design. The data collection techniques were conducted through ethnographic observation and interviews as well as document data. The results showed that the stone craft production in Muntilan is local wisdom that reflects the value of tolerance. Most of the rock artisans are Moslems, but they continued stone sculpture production that is part of the Hindhu-Buddist tradition. The product is oriented towards consumer demand, which is a contrast to the beliefs of sculptors such as Buddha statues, Hindu deities, statues of Jesus, as well as statues of other religions. The sculptures separated themselves between work and religious issues. It illustrates an open attitude as well as tolerance in accepting and understanding differences. Such local wisdom with a long-standing tolerance value in the community is a potential for community development in realizing a harmonious and peaceful life.